Unusual clinical case: extraluminal manifestation of a tapeworm from the eviscerated midline incision in a post-surgery patient - Ahmet Cem Dural; Muhammet Ferhat Celik; Baha Temizgonul; Mustafa Gokhan Unsal; Cevher Akarsu; Murat Gonenc; Mustafa Uygar Kalayci; Halil Alis (Journal of Infection in Developing Countries)
Taenia saginata infestation is one of the most common cestode infestations in humans, that may cause gastrointestinal tract related complications as a result of obstruction, perforation or anastomotic leakage. A 55-year-old male patient who was receiving palliative chemotherapy for stage IV gastric cancer was admitted to the emergency department for abdominal pain. A hollow viscus organ perforation was diagnosed and an emergency surgery was performed. On postoperative day 5, the patient’s midline incision eviscerated and a moving taenia emerged, with abundant particulated fluid from the incision line. The patient was admitted for abdominal surgery due to suspected bowel perforation. During the abdominal exploration, a relaxed purse stitch of the feeding tube was observed and no other bowel perforations were seen. The patient underwent two planned surgery for abdominal cavity lavage after the removal of cestode. Unfortunately, the patient  died sixteen days after his admission to the intensive care unit. This is the first case describing an extraluminal manifestation of a tapeworm in a midline incision from evisceration without intestinal perforation.